Managing Knowledge sebagai Sumber Daya untuk Kinerja Berkelanjutan melalui Innovation Capability di Masa Pandemic - Agung Sudjatmoko; Deni Hermana; Yulhendri Yulhendri; Daniel Kisahwan (Universitas Negeri Padang, 2021)
The ability to diversify the business for cooperatives according to the needs of members is a challenge. The goals of this research is to analyze knowledge management, innovation capability as a resource to build cooperative performance. The research method uses a quantitative approach to test the research hypothesis with data obtained through a survey of 230 cooperatives in Jakarta. The unit of observation is the employees and the members of the cooperative. Data analysis using SEM (structuration equation modeling). The results of the study confirm the importance of knowledge management and innovation capability to build performance. Transfer of knowledge to encourage innovation capability as one of the keys in knowledge management that leads cooperatives to sustainable performance. The theoretical implication is the development of the concept of a knowledge-sharing culture in a knowledge management system to realize performance. For cooperative managers, it is the development of knowledge management as a sustainable system and a culture of sharing to build superior cooperative performance. The research contribution is the development of the concept of knowledge as a resource to build performance excellence based on a sustainable perspective (RBV).